Fabrication and characterization of a novel self-assembling micelle based on chitosan cross-linked pectin–doxorubicin conjugates macromolecular pro-drug for targeted cancer therapy. Issue 22 (28th March 2018) - Li, Zhi-Ping; Jiang, Ming-Chao; Chen, Bo; Gao, Pei; Yang, Sa; Liu, Yu-Feng; Ye, Peng-Ju; He, Dong-Xiu; Huang, Hong-Lin; Yu, Cui-Yun
Abstract : Cancer is one of the leading causes of morbidity and mortality worldwide. Abstract : Cancer is one of the leading causes of morbidity and mortality worldwide. Doxorubicin is one of the most effective anticancer drugs approved by FDA. However, like all the other anticancer drugs, the efficacy of DOX is associated with high systemic toxicity to healthy tissues. In this study, chitosan cross-linked pectin–doxorubicin conjugates macromolecular pro-drug (CS-PDC-M) was prepared to enhance the therapeutic effects on liver cancer. CS-PDC-M was characterized in terms of size, size distribution, zeta potential, scanning electron microscope (SEM) and drug loading content. The CS-PDC-M achieved prolonged releasing ability was demonstrated by the in vitro drug release and in vitro cellular uptake assay. Biocompatibility of CS-PDC-M was screened by hemolysis activity examination, BSA adsorption test and cell viability evaluation in endothelial cells and LO2 cells. The CS-PDC-M achieved significantly high antitumor efficiency and targeting efficiency, which was demonstrated by the in vitro MTT assay and cellular targeting assay toward HepG2 cells, MCF-7 cells and A549 cells. The in vivo antitumor efficacy of CS-PDC-M was studied in athymic BALB/c nude mice bearing HepG2 cell xenografts. The organ damage assays of CS-PDC-M was studied in SD rats. Compared with that of free DOX and PDC-M, the CS-PDC-M exhibited higher antitumor efficacy and lower toxicity, implying that CS-PDC-M is a highly promising drug delivery system for hepatocellular carcinoma treatment.